1996
DOI: 10.1021/la9602022
|View full text |Cite
|
Sign up to set email alerts
|

On the Modification and Characterization of Chemical Surface Properties of Activated Carbon:  In the Search of Carbons with Stable Basic Properties

Abstract: Differences between the surface chemical properties of hydrogen-and nitrogen-treated samples of an activated carbon were quantified using several complementary techniques. Calorimetric studies conducted at 303 K revealed that the sample treated in N2 at 1223 K adsorbs a great deal of oxygen with unusually high differential heats. In fact, both the quantity and the heat of adsorption increased when the treatment temperature was raised from 773 to 1223 K. In contrast, samples treated in H2 adsorbed less and less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
230
0
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(263 citation statements)
references
References 37 publications
30
230
0
3
Order By: Relevance
“…13 All these effects can affect the surface active sites that are involved in the dehydrogenation and dehydration reactions of ethanol.…”
Section: Resultsmentioning
confidence: 99%
“…13 All these effects can affect the surface active sites that are involved in the dehydrogenation and dehydration reactions of ethanol.…”
Section: Resultsmentioning
confidence: 99%
“…The pH pzc value of acid treated OPSC was found to be around 4.7. It can be concluded that oxidization of oil palm shell charcoal with sulphuric acid yielded acidic surface since pH values of point of zero charge for these materials are at a lower pH range compared to the value reported for most chemically untreated commercial activated carbon (Menendez et al 1996). The surface acidity was due to the introduction of several oxygen-containing functional groups (Faria et al 2004 , the fraction of any particular species is dependent upon the chromium concentration and pH (Udaybhaskar et al 1990).…”
Section: Factors Influencing the Adsorption Of Cr (Vi) Ionsmentioning
confidence: 99%
“…Further exposure of oxidised carbons to CO 2 , N 2 or H 2 during temperature rating up to 1177°C can progressively eliminate specific (acid) surface oxide groups to obtain carbons with basic properties [82,100,167,174,177,178]. High temperature N 2 -reduction produced basic but reoxidisable surfaces at room temperature, whereas a reducing H 2 -atmosphere provided stable basic carbon surfaces [177]. Summarising the current knowledge on surface groups, surface oxides, in particular carboxylic, lactone, lactol, and phenolic groups, are mainly responsible for acidic carbon properties.…”
Section: Preparation and Characterisationmentioning
confidence: 99%
“…Summarising the current knowledge on surface groups, surface oxides, in particular carboxylic, lactone, lactol, and phenolic groups, are mainly responsible for acidic carbon properties. Basic properties are related to chromene and pyrone groups as well as to Lewis type sites in the graphite carbon matrix itself [100,108,[177][178][179].…”
Section: Preparation and Characterisationmentioning
confidence: 99%